2014
DOI: 10.1039/c4ra06175f
|View full text |Cite
|
Sign up to set email alerts
|

Effect of pretreatment on ceria-supported cobalt catalyst for ammonia synthesis

Abstract: Cerium in a catalyst may affect the catalytic reaction by providing surface hydroxyl groups. In this work, Co/ CeO 2 catalysts with different properties of hydroxyl groups were prepared using different pretreatment atmospheres during the heat treatment process of the hydroxide gel with metal and cerium. The heat treatment process of Co/CeO 2 precipitate in different pretreatment atmospheres was monitored by mass spectrometry. Pulse chemisorption measurements in combination with XRD, TPR, XPS, TEM were used to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
24
0
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 47 publications
(29 citation statements)
references
References 56 publications
2
24
0
1
Order By: Relevance
“…The obtained catalyst was then either treated with air or hydrogen for 4 h at 600 °C. [ 129 ] The ammonia formation rates at various temperatures and a pressure of 10 MPa are shown in Figure . They proposed the reaction pathway shown in Figure .…”
Section: Cobalt‐based Catalystsmentioning
confidence: 99%
“…The obtained catalyst was then either treated with air or hydrogen for 4 h at 600 °C. [ 129 ] The ammonia formation rates at various temperatures and a pressure of 10 MPa are shown in Figure . They proposed the reaction pathway shown in Figure .…”
Section: Cobalt‐based Catalystsmentioning
confidence: 99%
“…By way of illustration, it has been reported that defect engineering by a low-pressure thermal process instead of atmospheric pressure activation, could notably increase the concentration of oxygen vacancy defects and in turn, the CO oxidation activity of ceria nanoparticles, offering an additional tool towards the fine-tuning of MOs [200]. Moreover, it has been documented that the pretreatment protocol (oxidation or reduction) induces significant effects on the local surface structure of cobalt-ceria oxides affecting the dehydroxylation process in ammonia synthesis [202]. In a similar manner, oxidative pretreatment of cobalt-ceria catalysts resulted in an impoverishment of catalyst surface in cobalt species, due to the preferential existence of cerium species on the outer surface, whereas, cobalt and cerium species are uniformly distributed on the catalyst surface through the reduction pretreatment, which gives rise to the formation of oxygen vacancies [33].…”
Section: Pretreatment Effectsmentioning
confidence: 99%
“…The combination of ceria with transition metals, results in materials with excellent redox properties and surface oxygen mobility, reflected then on their catalytic activity. In this regard, cobalt-ceria mixed oxides have shown great potential in heterogeneous catalysis field as alternative to NMs-based catalysts, for several applications, such as: oxidation of volatile organic compounds (VOCs) [1,6,7], low temperature CO oxidation [8], soot oxidation [9], hydrocarbons (HCs) oxidation [10][11][12], NO oxidation [13], preferential oxidation of CO in the presence of H 2 excess (PROX) [14,15], ethanol steam reforming [16,17], iso-octane steam reforming [18], ammonia synthesis [19], among others.…”
Section: Introductionmentioning
confidence: 99%